ISOLATION AND CHARACTERIZATION OF MULTI DRUG RESISTANT UROPATHOGENIC ESCHERICHIA COLI FROM URINE SAMPLE OF URINARY TRACT INFECTED PATIENTS: Life Sciences-Microbiology - ROY, SOMENATH; MANDAL, DEBASIS; CHAKRABORTY, SUBHANKARI PRASAD; DASH, SANDEEP KUMAR (International Journal of Life Science and Pharma Research, 2012)
Abuse and improper prescribing policy of antibiotics causes remarkable increase of antibiotic resistance pattern among the E. coli isolates from Urinary Tract Infection (UTI). This study was conducted to isolate and identify multi drug resistant uropathogenic Escherichia coli from urine sample of urinary tract infected patients by convention and traditional techniques. Twenty two (22) UTI urine samples were collected from patients admitted to nearby hospitals. Characterization of isolated strains were determined by biochemical tests like Gram staining, indole, oxidase, catalase, methyl red, voges-proskauer, citrate utilization, hemolysis, motility; hydrolysis test of gelatin and urea; fermentation and utilization tests of glucose, lactose and sucrose. Sensitivity pattern of isolates were determined against some traditional and conventional antibiotics. From this study, it was revealed that 56.75% isolates were gram negative. Indole positivity was observed for 95.23% of Gram negative isolates. 100% of indole positive isolates were positive for catalse, methyl red, nitrate reduction, motility, hemolysis, carbohydrate fermentation on broth medium and carbohydrate utilization on Triple sugar iron agar. Negativity was seen for oxidase, Voges-Proskauer, urease, citrate, and gelatinase test. It was also observed that 100% of indole positive isolates gave positivity on differential media such as Mac Conkey agar and EMB agar. Antibiotic sensitivity indicates 100% of characterized strains were multi drug resistant. The findings of the study suggested that 20 uropathogenic E. coli were identified and all of them were multi drug resistant strains.